NADPH oxidase-mediated reactive oxygen species production activates hypoxia-inducible factor-1 (HIF-1) via the ERK pathway after hyperthermia treatment - Moon, EJ; Sonveaux, P; Porporato, PE; Danhier, P; Gallez, B; Batinic-Haberle, I; Nien, Y-C; Schroeder, T; Dewhirst, MW (National Academy of Sciences, 2010)
Hyperthermia (HT) is a strong adjuvant treatment with radiotherapy and chemotherapy because it causes tumor reoxygenation. However, the detailed molecular mechanisms of how HT enhances tumor oxygenation have not been elucidated. Here we report that 1 h of HT activates hypoxia-inducible factor-1 (HIF-1) in tumors and its downstream targets, vascular endothelial growth factor (VEGF) and pyruvate dehydrogenase kinase 1 (PDK1). Consistent with HIF-1 activation and up-regulation of its downstream genes, HT also enhances tumor perfusion/vascularization and decreases oxygen consumption. As a result, tumor hypoxia is reduced after HT, suggesting that these physiological changes contribute to HT-induced tumor reoxygenation. Because HIF-1 is a potent regulator of tumor vascularization and metabolism, our findings suggest that HIF-1 plays a role in HT-induced tumor reoxygenation by transactivating its downstream targets. We demonstrate that NADPH oxidase-mediated reactive oxygen species production, as a mechanism, up-regulates HIF-1 after HT. Furthermore, we determine that this pathway is initiated by increased transcription of NADPH oxidase-1 through the ERK pathway. In conclusion, this study determines that, although HIF-1 is a good therapeutic target, the timing of its inhibition needs to be optimized to achieve the most beneficial outcome when it is combined with other treatments of HT, radiation, and chemotherapy.